A single-molecule sequencing assay for the comprehensive profiling of T4 DNA ligase fidelity and bias during DNA end-joining. Issue 13 (8th May 2018) - Potapov, Vladimir; Ong, Jennifer L; Langhorst, Bradley W; Bilotti, Katharina; Cahoon, Dan; Canton, Barry; Knight, Thomas F; Evans, Thomas C; Lohman, Gregory J S
Abstract: DNA ligases are key enzymes in molecular and synthetic biology that catalyze the joining of breaks in duplex DNA and the end-joining of DNA fragments. Ligation fidelity (discrimination against the ligation of substrates containing mismatched base pairs) and bias (preferential ligation of particular sequences over others) have been well-studied in the context of nick ligation. However, almost no data exist for fidelity and bias in end-joining ligation contexts. In this study, we applied Pacific Biosciences Single-Molecule Real-Time sequencing technology to directly sequence the products of a highly multiplexed ligation reaction. This method has been used to profile the ligation of all three-base 5′-overhangs by T4 DNA ligase under typical ligation conditions in a single experiment. We report the relative frequency of all ligation products with or without mismatches, the position-dependent frequency of each mismatch, and the surprising observation that 5′-TNA overhangs ligate extremely inefficiently compared to all other Watson–Crick pairings. The method can easily be extended to profile other ligases, end-types (e.g. blunt ends and overhangs of different lengths), and the effect of adjacent sequence on the ligation results. Further, the method has the potential to provide new insights into the thermodynamics of annealing and the kinetics of end-joining reactions.